PENGAWASAN DAN PELAKSANAAN STRUKTUR BALOK DAN PLAT LANTAI PADA PROYEK PEMBANGUNAN GEDUNG PERPUSTAKAAN KABUPATEN BLITAR - Putri Salwa Adani Caecilia Kristiarini Luvitasari, S.T.; Hasan Dani (Universitas Negeri Surabaya, 2026)
This article documents the supervision and execution of beam and floor slab structural work at the Blitar Regency Library Building project, managed by the local Public Works and Spatial Planning Office (PUPR). Activities covered preparation, technical design, field implementation, and final evaluation. Data were gathered through direct site observation, technical literature review, mentoring sessions, and systematic report writing. Quality oversight followed ISO 9000 standards and project specifications requiring K-300 concrete with a slump of 12 ± 2 cm. Work was carried out in three sequential phases: formwork installation, steel reinforcement assembly, and concrete casting. Findings confirm that disciplined quality management consistently produced structural outcomes meeting specified technical requirements. Nevertheless, unpredictable field weather occasionally caused slump readings to deviate from acceptable limits, and project completion was delayed beyond the contracted timeline.